Sowing dates and node emission in buckwheat cultivars - Cargnelutti Filho, Alberto; Neu, Ismael Mario Márcio; Pezzini, Rafael Vieira; Dumke, Gabriel Elias; Somavilla, Felipe Manfio; Costa, Samanta Luiza da (Semina: Ciências Agrárias, 2021)
The aim of this study was to determine the rate of node appearance (RNA), the final number of nodes (FNN) and the period of node emission (PNE) in two buckwheat cultivars (Fagopyrum esculentum Moench) for different sowing dates, and to check variability in the RNA, FNN and PNE between the cultivars and sowing dates. The IPR91-Baili and IPR92-Altar cultivars were evaluated for 29 and 31 sowing dates from October to May in the 2017/2018 and 2018/2019 agricultural years respectively. In each experiment, a completely randomised design with five replications was used. The number of nodes (NN) on the main stem was counted twice a week in each plant (replication), from emission of the first node until the end of the cycle. The linear regression (y = a + bx) of the number of nodes (NN, y) was adjusted for each plant based on the number of days after emergence (DAE, x). The rate of node appearance (RNA), in days node-1, was determined from the inverse of the slope of the linear regression between NN and DAE (RNA = 1/b). The RNA was calculated for the period of node emission (PNE, in days), i.e. from emergence to emission of the last node. The final number of nodes (FNN) was counted at the end of node emission. Variability was found in the rate of node appearance (RNA), the final number of nodes (FNN) and the period of node emission (PNE) between the cultivars and sowing dates. The rate of node appearance ranges between 2.20 and 8.23 days node-1, the final number of nodes between 2.20 and 17.20, and the period of node emission between 16.60 and 49.20 days. Plants of the IPR91-Baili and IPR92-Altar cultivars show better vegetative development (lower RNA, higher FNN and greater PNE) when sown in November, December, January and February, compared to those sown in October, March, April and May.